Compairison of cultivars of annual ryegrass in lages, Santa Catarina, Brazil - Tcacenco, Fernando Adami (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out during the 1977 - 1979 period at the Lages Experiment Station of EMPASC, to compare thirteen cultivars of Italian ryegrass (Lolium multiflorum).The soil is a humic Cambisol; the climate is Cfb following Koeppen's classification. EMPASC 301 was the most productive cultivar on average over three years, and the one to present the best seasonal distribution of the production, since it concentrated its production during the winter. Most cultivars were unstable as far as the dry matter production during the 3-year period is concerned. The correlation coefficients between plant height and production ranged from 0.38 to 0.92, being higher for the cultivars with an erect growing habit. It can be concluded that cultivar EMPASC 301 is outstanding, as far as productivity and seasonal distribution are concerned. Although its production is unstable from year to year, this cultivar was always the most productive one. Cultivar Comercial was the second best in total production and in production during winter, and should be a valid alternative for the farmers in the region. It can also be concluded that plant height is a good estimator of dry matter production for those cultivars with erect growing habit.